Differences in the Binding to Fibrin of Urokinase and Tissue Plasminogen Activator - Thorsen, Sixtus; Glas-Greenwalt, Pia; Astrup, Tage (Thrombosis and Haemostasis, 1972)
When present during clot formation, tissue plasminogen activator (TA, porcine) is strongly bound to fibrin, in marked contrast to urokinase (UK, human). The amount of bound activator is approximately proportional to the total concentration of activator present, suggesting the formation of a dissociable complex between activator and binding sites on the fibrin. Frozen sections of plasminogen-free fibrin clots prepared in the presence of TA or UK, studied with the histochemical fibrin slide technique, showed sites of fibrinolytic activity related to fibrin strands in the clot. The activity caused by TA was more uniformly distributed along the fibrin strands than that caused by UK.